PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN PELANGGAN PERUSAHAAN LISTRIK NEGARA (PT. PLN PERSERO) CABANG KOTA KUPANG (STUDI KOMPARATIF: MASYARAKAT KELURAHAN OEBUFU DAN KELURAHAN OESAPA KOTA KUPANG) - Lausaka, Gracella Marice; Nursalam, Nursalam; Oktavianto, Aspri Budi (Journal Education and Government Wiyata, 2025)
This study aims to determine how the perceptions of the people of Oebufu Village and Oesapa Village towards the quality of services provided by the State Electricity Company (PT. PLN PERSERO) Kupang City Branch. The research uses a qualitative method using a comparative descriptive approach. In analyzing the problem the author relates the theory of service quality from Zeithaml (2005) which focuses on indicators, namely: Reliability, Assurance, and Empathy. The results of this study indicate that the public perception of Oebufu Village and Oesapa Village towards the quality of service from the State Electricity Company (PT. PLN PERSERO) Kupang City Branch has not fulfilled the applicable SOP. Regarding the timeliness of service, the community is often left waiting for a long and uncertain time, but the community feels that the attitude and behavior given during the service is polite and friendly.